Performance Analysis Methods in Smart Grids: An Overview - Salkuti, Surender Reddy (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2018)
This paper presents an overview of the performance analysis methods available for the Smart Grid (SG). Increased energy demand, volatile energy costs, uncertain power generation from the renewable energy resources (RERs), electric vehicles, and environmental concerns are coming together to change the nature of the traditional power grid. Many utility companies are now moving towards the smart metering and the Smart Grid solutions to address these challenges. Smart Grid is inclusive of advance tools, latest communication technologies and storage devices, which makes the Smart Grid vulnerable and complex. This paper aims to review the performance analysis of Smart Grid. It also presents various models of the Smart Grid performance indices. It presents the methods available for stability, reliability and resilience assessment in Smart Grid. It also describes the implementation approach using the real time tools and techniques.